Deleveraging Microfinance: Principles for Managing Voluntary Debt Workouts of Microfinance Institutions - Burand, Deborah (Journal of Law and Commerce, 2009)
Approximately 2.6 billion people, roughly 40 percent of the world’s population, live on less than $2 a day. 3 Of these people, 1.4 billion—that is one in four people in the developing world—live in extreme poverty subsisting on less than $1.25 a day. According to recent World Bank estimates, the financial and economic crisis facing the world today is likely to trap another 53 million people in extreme poverty.